(untitled) (Ustozlar uchun, 2025)
The theme "Modern Interactive Methods in Teaching Foreign Languages to Young Learners at Preschool Organizations" focuses on innovative, engaging, and child-centered approaches to language education. Interactive methods such as gamification, storytelling, role-playing, songs, digital tools, and Montessori-based activities help create a stimulating learning environment. These approaches cater to preschoolers’ natural curiosity and short attention spans, fostering active participation, social interaction, and experiential learning. This topic is relevant for early childhood educators, linguists, and curriculum developers, aiming to optimize language learning through play-based and immersive experiences. The study of these methods can help improve language fluency, cognitive development, and cultural awareness in young learners.